PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 7 PEMATANG PUDU DURI - Dewi Anggraini; Lazim N '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted because of the result of learning social study class IV SDN 7 P.Pudu. From 32 Students who achieve KKm just 14 Students (43,75%) while students who didn’t complete 18 students (56,25%) with an average 67,5. The purpose of this research to inprove learning out comes IPS class IV SDN 7 P.Pudu. with the application of learning models cooperative Student Teams Achievement Division (STAD) results obtained by the average value of 70,25 basic score in creased in the first cycle of 20,8% to 79,1 in the second cycle the average value of students also increased by 14,54% to 84,68 on the basic of completeness score IPS Student learning out comes is only 40% (finished). After the professor of applied learning model cooperative Student Teams Achievement Division (STAD). In the first cycle classical completeness increased 73,3% (not finished), the second cycle of classical completeness obtained are increased to increased 93,3%. Activities of teacher at the first meeting of 40,25% with both categories. The second meeting increased to 76,87% in both categories. In the second cycle increased to 84,68% with the category very well. At a meeting of the second of the second cycle. The activities of teacher increased to 87,5% with the category very well. Activities of students in the first cycle of the fisrt meeting activity students acquire a percentage of 68,7% in both categories. The second meeting of the fisrt cycle to 75% inboth categories. At the first meeting of the second cycle of student activity increased to 85,4% with the category very well, and at the second meeting of the second cycleinc reased again to 90 % with the category very well. Key Words: Cooperative Student Teams Achievement Division (STAD), Learning Outcomes IPS